Pemberdayaan Masyarakat Penyandang Disabilitas Melalui Program Corporate Social Responsibility (CSR) PT. KPI Unit VI Balongan Kabupaten Indramayu - Waneri, Uung; Setiawan, lham; Ibrahim, Ibrahim (Lembaga Yasin AlSys, 2025)
This study is motivated by the critical role of Corporate Social Responsibility (CSR) programs in promoting social inclusion, particularly for persons with disabilities who continue to face limited access to economic and social empowerment. The objective of this research is to analyze the social and economic impacts of the PERINTIS Program implemented by PT. KPI Unit VI Balongan, Indramayu Regency, on the empowerment of persons with disabilities, especially those with hearing and speech impairments. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis. The findings reveal that empowerment was carried out through four main pillars: Bina Manusia (capacity building and confidence enhancement through barista training and creative workshops), Bina Usaha (establishment of the